Dynamic characterization of biocomposites under high strain rate compression loading with split Hopkinson pressure bar and digital image correlation technique. (3rd July 2018) - Dave, Maharshi J.; Pandya, Tejas S.; Stoddard, Damian; Street, Jason
ABSTRACT: In this paper, dynamic response and energy absorption characteristics of three different types of wood-based biocomposites have been investigated using a split Hopkinson pressure bar (SHPB). Different types of biocomposite panel were produced using a Dieffenbacher hot press with a particular composition of refined cotton motes, pure cotton, and sweet potato flour. The strain induced in the specimen under dynamic stress equilibrium was obtained using the SHPB. Impact event at the zone of specimen was captured using a Shimadzu HPV-2 high-speed video camera. Digital image correlation (DIC) was performed using Proanalyst to obtain the strain in the specimen. Excellent agreement was found between the strains obtained using the SHPB and DIC analysis over three strain rates on three types of biocomposites. The biocomposite produced with cotton motes had the highest ultimate strength and specific energy absorption among three different types of biocomposites tested in this study.